2020
DOI: 10.3390/cancers12071876
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic Aminopeptidase Is a Novel Biomarker of Aggressive Chronic Lymphocytic Leukemia

Abstract: Treatment of chronic lymphocytic leukemia has advanced substantially as our understanding of the kinase signal transduction pathways driven by the B cell receptor (BcR) has developed. Particularly, understanding the role of Bruton tyrosine kinase and phosphatidyl inositol 3 kinase delta in driving prosurvival signal transduction in chronic lymphocytic leukemia (CLL) cells and their targeting with pharmacological inhibitors (ibrutinib and idelalisib, respectively) has improved patient outcomes significantly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…ANPEP is also expressed in a subset of Waldenström macroglobulinemia, MM, and plasma cell leukemias [9,10]. ANPEP expression in samples from MM patients has been shown to correlate with shorter overall survival [11,12]. Recently, endoplasmic reticulum aminopeptidase 2 (ERAP2) expression has been associated with a better outcome in patients with bladder cancer treated with immunotherapies [13].…”
Section: Introductionmentioning
confidence: 99%
“…ANPEP is also expressed in a subset of Waldenström macroglobulinemia, MM, and plasma cell leukemias [9,10]. ANPEP expression in samples from MM patients has been shown to correlate with shorter overall survival [11,12]. Recently, endoplasmic reticulum aminopeptidase 2 (ERAP2) expression has been associated with a better outcome in patients with bladder cancer treated with immunotherapies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been implicated in the metabolism of angiotensin peptides ( Chen et al, 2012 ), its biological and pathological roles remain poorly studied ( Chen et al, 2014 ). Recently it was found that DNPEP is a novel biomarker of aggressive chronic lymphocytic leukemia ( Kakodkar et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…SOX4 is a transcription factor involved in multiple biological processes, including cell proliferation, differentiation, and migration [ 13 ]. MAPK1, a kinase, is pivotal in numerous signaling pathways [ 14 ]. IQGAP1 is a versatile protein involved in cell cytoskeleton remodeling, cell migration, and intercellular signaling [ 15 ].…”
Section: Introductionmentioning
confidence: 99%